2021
DOI: 10.1111/cei.13626
|View full text |Cite
|
Sign up to set email alerts
|

A single-center pilot study in Malaysia on the clinical utility of whole-exome sequencing for inborn errors of immunity

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The genetic heterogeneity of the IEI as well as the delay in the diagnosis in atypical cases leads to significant morbidity and mortality. Establishing definitive genetic diagnosis is very important for patients’ management [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic heterogeneity of the IEI as well as the delay in the diagnosis in atypical cases leads to significant morbidity and mortality. Establishing definitive genetic diagnosis is very important for patients’ management [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the International Union of Immunological Societies (IUIS), a total of 485 IEIs have been reported arising from defects in more than 490 genes [ 2 ]. The use of next-generation sequencing (NGS), particularly whole-exome sequencing (WES), has improved clinical diagnosis and unraveled novel genes and variants underlying IEIs [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies reported successful use of WES to identify genetic mutations for several types of monogenic disease that belong to the group of inborn errors of immunity ( 17 , 18 ). In the present study, the application of WES to ADPKD was evaluated.…”
Section: Introductionmentioning
confidence: 99%